Evaluation of Knowledge, Attitude, and Practice of pharmacovigilence and adverse drug reactions among the healthcare professional in Bastar region of Chattisgarh (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
BackgroundOne of global problem encountered nowadays is adverse drug reaction, which affect the majority of population both the children and adults.  Adverse drug reactions (ADRs) are the consequences of drug therapy, and it is fourth leading cause of morbidity and mortality in world. Pharmacovigilence plays an important role in the reduction of ADRs. Voluntary reporting of ADRs by health care professional is an important tool in the success of pharmacovigilence programme. So this study was conducted to assess the awareness of pharmacovigilence and to evaluate the knowledge, attitude and practices among doctors in tertiary care teaching hospital in Bastar region of Chhattisgarh in India.MethodsA cross-sectional questionnaires based study was carried out among doctors of tertiary care teaching hospital with Govt. Medical College Jagdalpur. 85 doctors (physician) Were enrolled in our study. A Prevalidated 21 questionnaires of knowledge, attitude and practice towards Pharmacovigilance were developed and after taking inform consent, questionnaires were directly distributed to the physician, 7-8 days time was given to fill the form. The filled KAP questionnaires were analyzed question wise and their percentage value was calculated by Microsoft excel and graph pad prism version 6.01.ResultIn our study  120  questionnaires were distributed  to healthcare professional of  tertiary care teaching hospital of which 85(70.8%) responded , in which 45 consultant were  from different clinical department  and 40 intern were filled form and sent  it back .ADRs reporting was considered very important by almost all of them ,but actual practice was lacking as only 10.5 % had reported any ADR .ConclusionThe healthcare professional were  aware of the importance of ADR reporting, but lack of knowledge about the procedure  where to report ,whom to report ,unavailability of ADR reporting form, uncertain association  are the most common cause of underreporting. So there is need to conduct an awareness programme about the pharmacovigilence as it is tertiary care center for patients safety.